1993
DOI: 10.1177/41.11.7691930
|View full text |Cite
|
Sign up to set email alerts
|

Antigen retrieval technique utilizing citrate buffer or urea solution for immunohistochemical demonstration of androgen receptor in formalin-fixed paraffin sections.

Abstract: We developed a staining protocol for demonstration of androgen receptor (AR) in formalin-fixed, paraffin-embedded tissue sections. The method is based on the antigen retrieval microwave (MW) heating technique. Results are compared with different types of enzyme digestion pre-treatments. The strongest immunostaining signal and clearest background were obtained by MW heating of dewaxed paraffin sections in 5% urea or citrate buffer solution (pH 6); pure distilled water gave less consistent results. Enzymatic dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(177 citation statements)
references
References 11 publications
2
173
1
1
Order By: Relevance
“…Coronal serial sections (7 m) were mounted on poly-L-lysine-coated slides (Sigma, St Louis, MO, USA) and allowed to air-dry, for 16 h at 45°C, deparaYnized, rehydrated, and treated for immunocytochemistry, as described before (Calle et al, 2005a). As to the Fos staining, the antigen retrieval method of Shi et al (1993) was used. After deparaYnization, sections were pre-heated in a microwave oven at 90°C in 0.3% tri-sodium citrate buVer (pH.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Coronal serial sections (7 m) were mounted on poly-L-lysine-coated slides (Sigma, St Louis, MO, USA) and allowed to air-dry, for 16 h at 45°C, deparaYnized, rehydrated, and treated for immunocytochemistry, as described before (Calle et al, 2005a). As to the Fos staining, the antigen retrieval method of Shi et al (1993) was used. After deparaYnization, sections were pre-heated in a microwave oven at 90°C in 0.3% tri-sodium citrate buVer (pH.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Therefore the accessibility of antigenic epitopes might be limited. Such hindrances may be partially reversed by retrieval techniques like enzyme digestion and microwave oven heating [28][29][30]. To identify a suitable method for antigen retrieval, the effect of pretreatment with enzyme and microwave oven heating was studied in tissues from eight mice in the following three experiments:…”
Section: Gf ¼mentioning
confidence: 99%
“…It has been demonstrated that the AR technique is a simple and effective enhancement method for immunohistochemistry on archival tissue sections. Two major advantages of AR-IHC are (a) reduction of the detection thresholds of immunohistochemical staining (increased sensitivity) for a wide range of antibodies, and (b) retrieval of some antigens, such as Ki-67, MIB1, ER-1D5, bcl-2, androgen receptor, RB, CD5, CD8, CD35, CD38, CD25, CD45R, CD34, CD68, CD44, CD55, VCAM-1, CGA7 (smooth muscle-specific actin), CD19, and thrombospondin (Grossfeld et al 1996;Cuevas et al 1994;Cattoretti et al 1993;Gown et al 1993a;Leong and Milios 1993;Shi et al 1993bShi et al ,1996, which are otherwise negative even with other unmasking pretreatment. At present the AR-IHC method is being widely used for the detection of ER, PR, MIB1, p53, bcl-2, pRB, and some CD markers on routinely formalin-fixed, paraffin-embedded tissue sections in daily pathological diagnosis (for review and detailed data see Shi et al 1995b).…”
Section: Applicationmentioning
confidence: 99%
“…Furthermore, the toxic effect of metal salts, particularly lead salts, is a major drawback. Therefore, several alternative AR solutions were subsequently developed, such as citrate, Tris and other buffer solutions, and urea (Kawai et al 1994b;Taylor et al 1994a;Gown et al 1993a;Leong and Milios 1993;Shi et al 1993b;Gerdes et al 1992), EDTA or EGTA (Morgan et al 1994), glycine-HCl buffer (Imam et al 1995), and periodic acid (Kwaspen et al 1995).…”
Section: The Effect Of Metal Ions the Chemical Composi-mentioning
confidence: 99%